48th Annual International Conference of Young Scientists "Cold in biology and medicine: current problems in cryobiology, transplantology, and biotechnology", Kharkiv, May, 15–16 2024 - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):287–289